Conductor size selection in low voltage networks under distributed energy resource uncertainty - Waswa, Lewis Sakwa (Stellenbosch : Stellenbosch University, 2025)
Waswa, L. S. 2025. Conductor size selection in low voltage networks under distributed energy resource uncertainty. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/95da4468-231b-4161-95a9-d3b93925feda